2007
DOI: 10.2522/ptj.20070017
|View full text |Cite
|
Sign up to set email alerts
|

Gross Motor Development of Children With Hurler Syndrome After Umbilical Cord Blood Transplantation

Abstract: The participants had varying degrees of delay in different gross motor domains. While gaining new gross motor abilities over time, these children continued to have delays up to 48 months after UCBT. Physical therapists treating children with Hurler syndrome after UCBT should use assessment tools that will capture these differences and should individualize treatment plans accordingly. Additional research is needed to document the efficacy of physical therapy intervention with this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…All of these studies addressed one of three aspects of gait: 1) development of independent walking in toddlers, 2) quality of gait, and 3) independent gait and mobility in late childhood/ adolescence. With respect to independent walking, four studies reported a delayed onset (Hugh-Jones 1986; Dusing et al 2007a; Ringden et al 2006; Dusing et al 2007b). This developmental delay was attributed to limited practice during hospitalisation for HSCT, in addition to orthopaedic abnormalities (Dusing et al 2007a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these studies addressed one of three aspects of gait: 1) development of independent walking in toddlers, 2) quality of gait, and 3) independent gait and mobility in late childhood/ adolescence. With respect to independent walking, four studies reported a delayed onset (Hugh-Jones 1986; Dusing et al 2007a; Ringden et al 2006; Dusing et al 2007b). This developmental delay was attributed to limited practice during hospitalisation for HSCT, in addition to orthopaedic abnormalities (Dusing et al 2007a).…”
Section: Resultsmentioning
confidence: 99%
“…Other aspects that contribute to motor functioning are the development of gross and fine motor skills. These were generally studied on a group level, using developmental scales such as the Vineland Adaptive Behavior Scales (VABS) (Bjoraker et al 2006), Peabody Developmental Motor Scales, edition 2 (PDMS-2) (Dusing et al 2007a;Dusing et al 2007b;D u s i n ge ta l .2005), Denver Developmental Screening Test (DDST) (Lucke et al 2007), and the more recently developed MPS-PPM (MPS physical performance measure) (Dumas et al 2004). Evaluation of these five studies, including a total of 63 patients, showed that Hurler patients were limited in their gross motor development and had mild to pronounced motor retardation between 0 and 4 years of age, when compared to age-referenced controls.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…CD34+ cells have been used for treating malignant diseases such as MI [5–9, 18, 19], hematological malignancies [20–22], Hurler syndrome [23, 24], Krabbe disease [25], primary immunodeficiency diseases [26], bone marrow failure [27], and β‐thalassemia [28]. Along with the advantages, CD34+ cells also have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Com relação à paciente estudada, ela apresentava baixo desempenho tanto na motricidade global como nas habilidades finas em relação ao esperado para a sua IC. Dados semelhantes são referidos em outros estudos sobre desenvolvimento motor na MPS tipo 1 (5,6,11,12) . A deficiência na fase de aquisição das habilidades motoras decorre das lesões do sistema central e da falta de experiências sensório-motoras, dificultando, assim, a capacidade de planejamento e, consequentemente, a execução das habilidades propostas (7,10) .…”
Section: Discussionunclassified
“…Caracteriza-se por ser doença multisistêmica e progressiva, com anormalidades ósseas, atraso no desenvolvimento neuromotor (2) , além de complicações cardíacas resultantes da elevada deposição de GAGs nas artérias coronárias e válvulas cardíacas (1,3) . Apesar do atraso motor evidente nos pacientes acometidos, os relatos acerca das características motoras e funcionais são escassos, e o conhecimento desse aspecto da doença vem aumentando mais recentemente, após o advento da intervenção medicamentosa (4)(5)(6) . A influência do tratamento fisioterapêutico na MPS tipo 1 não é descrita em pesquisas científicas, sendo tal intervenção prescrita para otimizar a funcionalidade e a autonomia de crianças portadoras da doença.…”
Section: Introductionunclassified